Performance-Based Pay: An Empirical Study in Malaysian Federal Government Linked Companies, Kuching, Sarawak (Malaysian Management Journal, 2008)
Compensation management literature highlights that properly administering performance-based pay may directly affect employee attitudes and behaviours (i.e. job performance and job turnover). Furthermore, a thorough review of such relationships revealed that the effect of performance-based pay on such employee attitudes and behaviours is indirectly affected by perceptions of procedural justice. The nature of this relationship is less emphasised in past research studies. Therefore, a survey method was used to gather 124 usable questionnaires from employees who have worked in the Malaysian Federal Government linked companies in Kuching, Sarawak (GLCKUCHING). A stepwise regression analysis was performed to determine the mediating effect of procedural justice and the findings obtained indicated that procedural justice and performance-based pay were significantly correlated with job performance. However, no significant correlation was found between procedural justice and performance-based pay with job turnover. Results of this study serve as evidence confirming the assertion that procedural justice does act as a partial mediating variable in the performance-based pay models of the organizational sector investigated. This paper also addresses the implications of such findings on compensation theory and practice. In addition, conceptual and methodological limitations, and directions for future research are also discussed.